2010
DOI: 10.1515/cclm.2010.227
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutant-enriched liquidchip technology for the qualitative detection of somatic mutations in KRAS gene from both serum and tissue samples

Abstract: A novel, qualitative, sensitive, reliable and high throughput liquidchip technology has been developed for detecting KRAS mutations using clinical serum and formalin-fixed and paraffin-embedded samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Based on the prevalence of gene mutations and molecular segmentation in other tumor types (as well as our previously published data; Hou et al), 34 'hot spot' EGFR, K-ras, B-raf, and PIK3CA gene mutations were screened for using the mutant-enriched PCR method. 35 The method was performed by SurExam Bio-Tech Co. Ltd., Guangzhou Technology Innovation Base, Science City, Guangzhou, PRC. Positive results were further confirmed by PCR-direct sequencing.…”
Section: Her2 Fluorescencementioning
confidence: 99%
“…Based on the prevalence of gene mutations and molecular segmentation in other tumor types (as well as our previously published data; Hou et al), 34 'hot spot' EGFR, K-ras, B-raf, and PIK3CA gene mutations were screened for using the mutant-enriched PCR method. 35 The method was performed by SurExam Bio-Tech Co. Ltd., Guangzhou Technology Innovation Base, Science City, Guangzhou, PRC. Positive results were further confirmed by PCR-direct sequencing.…”
Section: Her2 Fluorescencementioning
confidence: 99%
“…Many technologies are available for analyzing circulating nucleic acid [16,17]. MeL technology was developed by Wu [18] to detect KRaS mutations using serum or formalin-fixed and paraffin-embedded samples. The technique is a method of high sensitivity, high reliablity and high throughput [18].…”
Section: Resultsmentioning
confidence: 99%
“…MeL technology was developed by Wu [18] to detect KRaS mutations using serum or formalin-fixed and paraffin-embedded samples. The technique is a method of high sensitivity, high reliablity and high throughput [18]. In the current study, a very low egfR mutation rate was found (1/35, 2.8%), which was consistent with reports in literatures [11][12].…”
Section: Resultsmentioning
confidence: 99%
“…Actually, Denys et al [18] also used LNA-modified oligonucletoide probes for JAK2 V617F detection and improved the sensitivity of the real-time PCR assay to 0.4% mutant allele. In our opinion, further reliable improvement of sensitivity of the bead-based assay below 1% mutant allele would be possible through mutant enrichment by initial two-step PCR amplification with intermediate BsaXI restriction, similar to the approach reported for KRAS mutation detection [19].…”
Section: (Received 11 April 2011; Accepted 24 April 2011)mentioning
confidence: 88%